Aliran-Aliran Pemikiran Alternatif Dalam Akuntansi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRACT This paper discusses the school of thinking within the accounting circle other than structural functionalism which is the mainstream. The other alternative schools discussed that influenced the accounting development are interpretivism, radical structuralism, radical humanism, and postmodernism. Key words: accounting schools, structural functionalism, interpretivism, radical structuralism, radical humanism, postmodernism.